2022
DOI: 10.1093/heapro/daac012
|View full text |Cite
|
Sign up to set email alerts
|

Change in health, wellbeing and physical activity levels during the COVID-19 pandemic: a longitudinal cohort of parkrun participants in the United Kingdom

Abstract: Summary Lockdown restrictions imposed across the UK in response to the coronavirus disease 2019 (COVID-19) pandemic had a profound impact on many people’s health and wellbeing. People were encouraged to be active, but population surveys suggest some groups found this easier than others. We explored the changes in health, wellbeing and physical activity levels among a sample in the UK who experienced the sudden loss of a weekly community-based physical activity opportunity, parkrun. A sample of U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
3
6
0
Order By: Relevance
“…The findings are consistent with previous studies that have identified that COVID-19 pandemic lockdowns reduced levels of physical activity particularly for the young, the less fit and those in most deprived areas [49,29]. The current study has identified that these patterns have continued into the post-lockdown period in a mass participation event in Scotland.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The findings are consistent with previous studies that have identified that COVID-19 pandemic lockdowns reduced levels of physical activity particularly for the young, the less fit and those in most deprived areas [49,29]. The current study has identified that these patterns have continued into the post-lockdown period in a mass participation event in Scotland.…”
Section: Discussionsupporting
confidence: 92%
“…A survey of the behaviour of previous parkrun participants during lockdown found reduced activity levels [29]. Increased inactivity during lockdown was particularly evident in younger adults, people in deprived areas and the least active [29]. Consequently, the changing patterns in activity among parkrun participants during lockdown are consistent with those identified in other studies [4][5][6][7][8] revealing the potential value of using parkrun as a model system.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…The results of this study revealed that female students value their autonomy, personal growth, and purpose in life higher than male students. According to other researchers, the Coronavirus pandemic affected female students more, with an increased level of anxiety being one of the discrete emotions noticed among students during the Coronavirus pandemic, especially among female students, compared to the pre-pandemic period [ 31 , 32 ]. Students who felt high levels of psychological well-being were more likely to choose active coping styles, while those with lower PWB were more likely to choose avoidance-type coping strategies [ 33 ].…”
Section: Discussionmentioning
confidence: 99%